Strategi daya tindak remaja sekolah dan hubungannya dengan kemurungan - Ferlis Bullare @ Bahari,; Rosnah Ismail,; Lailawati Madlan @ Endalan,; Surianti Lajuma, (Penerbit Universiti Kebangsaan Malaysia, 2015)
The purpose of this paper is to explore the types of coping strategies to overcome daily obstacles and depression which are practicing by secondary school students in Sabah. Specifically, this survey study is conducted to 1) compare the types of coping strategies and depression based on the gender and the educational level of students, 2) the relationship between the types of coping strategies and depression levels. A total of 2746 students ranging from 13 to 19 years old from 18 secondary schools in Sabah had been chosen as respondents. The Adolescent Coping Scale (ACS) (1993) is used to measure the coping strategies of students and the Beck Depression Index-II (BDI-II) (1996) is to measure the students’ level of depression. Data collected were analyzed using descriptive statistics (frequencies, percentage, mean and standard deviation) while the independent sample t-test and Pearson correlation were used to test the inferential statistics. The result indicated that there were differences in types of coping strategies between gender and educational level (i.e. lower secondary and upper secondary). Result also showed that there was a significant relationship between coping strategies with the students’ level of depression. Hence, several implications and suggestions are highlighted in this paper.